أثره البعد "الانفصالي" في علاقة سورية مع الكرد خلال الأزمة - جبور مازن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تحاول هذه الدراسة البحث في العلاقة بين دمشق وكردها من خلال توضيح الوضع السياسي والاقتصادي والاجتماعي والعسكري في منطقة الجزيرة، البيئة التي يتمتع فيها الكرد بنسبة التواجد الأكبر قياساً بباقي الجغرافية السورية، إلا أنهم يبقون أقلية مقارنة بالسكان العرب للمنطقة، ومن ثم تتبع الدراسة التعاطي الكردي مع الأزمة السورية باعتبارها فرصة لتحقيق حلم قديم، في حين أن الدولة السورية بنت استراتيجياتها باعتبارهم جزء لا يمكن الاخلال به من المجتمع السوري، إلا أن الكرد بتنظيماتهم السياسية والعسكرية كانوا يغردون خارج السرب السوري العام، وكانت لهم حقيقة مخالفة لما دأبوا على أن يلمحوا به من خلال تسمياتهم. وتخلص الدراسة إلى أنه لم يكن انسحاب الجيش العربي السوري من محافظتي الرقة والحسكة، بموجب اتفاق مع التنظيمات الكردية الموجودة هناك، بل جاء في إطار استراتيجيات عسكرية، وتحت وطأة ضغوط من قبل المعارضة المسلحة التي تدعمها دول إقليمية وغربية في مقدمتها فرنسا وتركيا، فجاءت الفرصة التي وجدها الكرد سانحة لتحقيق أحلامهم بإنشاء كيان انفصالي. This study attempts to study the relationship between Damascus and the Syrian Kurds by clarifying the political, economic, social and military situation in Al-Jazeera region (north Eastern Syria), and the environment in which the Kurds have the largest presence relative to the rest of the Syrians geographical distribution. However, they remain a minority in comparison with the Arab population of the region. The Syrian crisis formed an opportunity to achieve an old dream, in a time that the Syrian state arranged its strategies as integrated Syrian society could not be disrupted. However, the Kurds political and military organizations were chanting outside the Syrian general squadron different song sought after a different reality with different names. The study concluded that the Syrian Arab Army’s withdrawal from Raqqa and Hasaka provinces, was not executed under an agreement with the Kurdish organizations there. It was in the context of military strategies, and under the pressure of the armed opposition supported by regional and Western countries led by France and Turkey. The Kurds found it is a possible opportunity to realize their dream for creating a separatist entity.